THE IDEA OF GASSĀN HAMDŪN IN THE BOOK TAFSĪR MIN NASAMĀT AL-QUR'ĀN KALIMĀT WA BAYĀN - Abdullah, Hadrawi; Galib, Muhammad; Sabry, Muhammad Sadiq (Program Pascasarjana, UIN Alauddin Makassar, 2022)
The purpose of this study is to find out the Idea of Gassan Hamdun in the book of Tafsir Min Nasamat al-Qur'an Kalimat wa Bayan which relates to interpretation techniques, writing systematics and their characteristics, advantages and disadvantages of the book. The results of this study show that Gassan Hamdun used the Ijmali method in interpreting verses from the Qur'an by being sourced from the tafsir bi al-ma'syour and other major tafsir books such as Tafsir Jalalain Tafsir Imam Nasafi, Tafsir Al-Alusi, Tafsir Ibn Kasir, Al-Jami' Li Ahkam al-Qur'an